Memahami Konsep Dasar Teori Bahasa dan Pembelajaran Bahasa - Mamluatun Ni'mah (At- Ta'lim : Jurnal Pendidikan, 2016)
The distinction of method and ways in teaching languange is influenced by the distinction of views on languange meaning and the distinction of ways of analysis and how to describe the langauage. There are two important perspectives in language theory –linguistics–, they are structural and transformative-generative. On the other hand, the language teaching is based on the phsychological theory and linguistics. The physichologist resulted two different views, they are behaviorism and cognitivism. Besides the two views, there is one more view which is called constructivism.